2006
DOI: 10.1111/j.1600-0625.2006.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin‐induced apoptosis in human keratinocytes is caspase‐8 dependent and accompanied by mitochondrial cytochrome c release

Abstract: Cyclodextrins (CDs) are cyclic oligosaccharides that are able to form inclusion complexes with a variety of substances. For pharmaceutical applications, CD‐based drug formulations offer important advantages compared with uncomplexed drugs. These include improved water solubility of lipophilic drug molecules, increased chemical stability, as well as enhanced bioavailability and absorption rate. Also, a number of topical formulations for dermal and transdermal drug delivery contain CDs. However, the most frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 53 publications
1
22
1
Order By: Relevance
“…This is because there was a report that MBCD could induce apoptosis in human keratinocytes [16], while HPBCD does not have that effect [9]. Furthermore, when administered orally, absorption of HPBCD is better than that of MBCD [8].…”
Section: Dg-bcd-abt Caused Tumor Regression In Micementioning
confidence: 99%
“…This is because there was a report that MBCD could induce apoptosis in human keratinocytes [16], while HPBCD does not have that effect [9]. Furthermore, when administered orally, absorption of HPBCD is better than that of MBCD [8].…”
Section: Dg-bcd-abt Caused Tumor Regression In Micementioning
confidence: 99%
“…8 ). These findings may provide further rational use of cyclodextrins in topical formulations for dermal and transdermal drug delivery, or textiles for medical applications [19] .…”
Section: Measurement Of Biocompatibility and Cytotoxicitymentioning
confidence: 99%
“…It is reported that β-CD and M-β-CD induce caspasedependent apoptotic cell death in human keratinocytes on depletion of membrane cholesterol, whereas α-CD, γ-CD, and HP-β-CD are not apoptotic to this type of cell (Schönfelder et al, 2006).…”
Section: What Is the Safety Record Of Cyclodextrins?mentioning
confidence: 99%